Risk of HIV Transmission Through Sexual Activities: A Survey among Hiv-Positive Gay Men in Jember, Indonesia - Dicky Endrian Kurniawan; Lantin Sulistyorini; Kholid Rosyidi Muhammad Nur; Muhammad Nur Khamid; Alfid Tri Afandi; Retno Purwandari; Anisah Ardiana (Nursing and Health Sciences Journal (NHSJ), 2021)
Introduction: Prevention of HIV transmission can be done through safe sexual activities. It can occur if HIV-positive gay men or men who sex men (MSM) did not have sex with men or use a condom. Objective: This study aimed to identify the preventive behavior of HIV transmission through sexual activities among HIV-positive gay men. Methods: This study used a quantitative design with a descriptive exploratory approach. One hundred and one HIV-positive gay men were collected by using purposive sampling following this study. Data were collected by a questionnaire of preventive behavior of HIV transmission through sexual behavior and analyzed with an exploratory, descriptive approach. Results: Almost all MSM still have sex (96%) after they have been diagnosed HIV-positive, and most do not always use a condom (74.3%). Conclusions: Sexual prevention behavior in MSM is still low and it can increase new HIV cases. Efforts are needed against HIV transmission among the gay men population by adequate information to enhance condom use awareness and commitment when they have the same sexual activities.